Desenhar a minha casa: entre razão e empatia - Eliana Pereira dos Santos (2022)
The constitution of a house is something that goes beyond its initial physical materialization. More than a box with doors and windows, the house should serve as someone's home. Architects design houses, in which people in turn build their sense of home, based on more emotional aspects such as memories and desires. From this point of view, the design of a house is, perhaps, the most challen-ging design exercise of all and the one that requires greater sensitivity, because when designing a house it is necessary that it becomes the basis for his future inha-bitant's home. From the outset, architects with their training have the tools and knowledge necessary to respond to this very complex challenge. Although designing the house for others implies the added difficulty of being able to interpret their ne-eds, when the role of architect and client coincide, there is a special opportunity for a reflection on the relationship between home and house. The present work aims to reflect on how to design a house that allows the installation of a home. For this, based on memories of my grandparents' house, which meant a second home for me, and reflection on specific case studies, I will try to find the premises to design my house, capable of receiving my personal territory in the future, that is, my home.